Charting progress towards system-scale ecosystem service valuation in islands - OLESON, KIRSTEN L.L.; GRAFELD, SHANNA; VAN BEUKERING, PIETER; BRANDER, LUKE; JAMES, PHILIP A.S.; WOLFS, ESTHER (Environmental conservation, 2018)
Using islands as a model system, this paper seeks to understand how ecosystem service valuation (ESV) has and can move from a monetized, single-service paradigm to an integrated valuation paradigm, a participatory approach that represents a more diverse set of the values of nature, and beyond, to a more fully realized conception of the island social–ecological systems. A systematic literature review of 314 island ESV studies reveals developments in the design, implementation and adoption of ESV studies over time. We complement the review with three cases where this evolution is happening, thereby offering insights into successful means of translating ESV into information useful for island system-scale management, policy design and planning. Over the past 30 years, both the number of studies and the number of services addressed per study have steadily grown, and valuation methods have become more inclusive of multiple values. The cases reveal lessons for ESV practice. Insights are that ESV should increasingly: (i) recognize strong interconnections between ecosystems and between human and environmental systems; (ii) move towards more integrated valuation methods that better capture the diverse values of nature; and (iii) be based on an iterative process where knowledge and decision-support tools are co-created with decision-makers and stakeholders.